Short-Term Impacts of Low-Level Jet Fighter Training on Caribou in Labrador - Harrington, Fred H.; Veitch, Alasdair M. (ARCTIC, 1991)
The short-term impacts on caribou (Rangifer tarandus) of low-level jet fighter training activity at Canadian Forces Base Goose Bay (Labrador) were investigated during the 1986-88 training seasons (April-October). Visual observations of low-level (30 m agl) jet overpasses indicated an initial startle response but otherwise brief overt reaction by woodland caribou on late-winter alpine tundra habitat. Between 1986 and 1988, daily effects of jet overflights were monitored on 10 caribou equipped with satellite-tracked radiocollars, which provided daily indices of activity and movement. Half the animals were exposed to jet overflights; the other 5 caribou were avoided during training exercises and therefore served as control animals. In 1988, the control caribou were from a population that had never been overflown. Level of exposure to low-level flying within the exposed population did not significantly affect daily activity levels or distance travelled, although comparison with the unexposed population did suggest potential effects. The results indicate that significant impacts of low-level overflights can be minimized through a program of avoidance.Key words: caribou (Rangifer tarandus), low-level flying, jet aircraft, helicopters, disturbance, activity, movements, Labrador Mots clés: caribou (Rangifer tarandus), vol à basse altitude, avion à réaction, hélicoptères, perturbation, activité, déplacement, Labrador.